THE INFLUENCE OF PRICES ON PURCHASE INTEREST IN PURCHASE IN BASMALLAH STORE SUMBERJAMBE DISTRICT JEMBER REGENCY - Khoirul Anam; villatus sholikhah (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2021)
During the Covid-19 pandemic, the global economy has decreased. there are so many places of business that have to go out of business because of the impact of the pandemic. However, besides that, there are still places of business that are able to maintain their existence and continue to develop their business. One of them is the Basmalah shop which is a branch of the Sidogiri Islamic Boarding School Cooperative. The Basmalah store has E-Maal facilities that can make it easier for consumers to save and get discounted prices by using the E-Maal card in shopping on certain days. The focus in this study is whether the price has an influence on people's buying interest in the Basmalah store. This study uses a quantitative approach. The test results show that the effect of price on buying interest has a significance value of 0.004 0.05 and a tcount of 2.981 2.011 rtable, so it can be concluded that the hypothesis that there is a significant effect of the product on buying interest is accepted. This means that the product variable has a significant influence on buying interest at the Basmallah Store, Sumberjambe District, Jember Regency